Acutely infected teeth: to extract or not to extract? - Bozkurt Kubilay Isik; Gökhan Gürses; Dilek Menziletoglu (Brazilian Oral Research, 2018)
Abstract: Not only laymen but also dentists generally believe that extraction of acutely infected teeth should be avoided until the infection subdues by using systemic antibiotics. The aim of this study was to compare perioperative complications in routine extractions of acutely infected teeth with extractions of asymptomatic teeth. This prospective study was performed with 82 patients. Severe pain on percussion of the relevant tooth was considered as basic criteria for acute infection. The acutely infected teeth were labeled as the study group (n = 35) and the asymptomatic teeth as the control group (n = 47). The extractions were done using standard procedures. The amount of anesthetic solution used and duration of extractions were recorded. Postoperative severe pain and exposed bone with no granulation tissue in the extraction socket were indications of alveolar osteitis (AO). The level of statistical significance was accepted as 0.05. Symptoms that could indicate systemic response, including fever, fatigue, and shivering were not found. There was no statistically significant difference between groups in terms of AO, amount of anesthetic solution used, and duration of extraction. The presence of an acute infection characterized by severe percussion pain is not a contraindication for tooth extraction. Infected teeth should be extracted as soon as possible and the procedure should not be postponed by giving antibiotics.